2012
DOI: 10.1128/mcb.06771-11
|View full text |Cite
|
Sign up to set email alerts
|

Cks1 Promotion of S Phase Entry and Proliferation Is Independent of p27Kip1 Suppression

Abstract: Cks1 is an activator of the SCF Skp2 ubiquitin ligase complex that targets the cell cycle inhibitor p27 Kip1 for degradation. The loss of Cks1 results in p27 Kip1 accumulation and decreased proliferation and inhibits tumorigenesis. We identify here a function of Cks1 in mammalian cell cycle regulation that is independent of p27 Kip1 . Specifically, Cks1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In this context it also has to be noted that loss of Cks1, but not loss of Skp2, results in a significant delay in tumorigenesis in the same Myc lymphoma model, 35,39 and that Cks1 has cell cycle regulatory functions independent of p27 suppression. 19 We also found that under cell culture conditions which stimulate HSC to be recruited into the cell cycle, Cks1 deficiency promotes cell death of MPs upon growth factor withdrawal. One possible explanation could be the accumulation of p27, as p27 Figure 2c).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In this context it also has to be noted that loss of Cks1, but not loss of Skp2, results in a significant delay in tumorigenesis in the same Myc lymphoma model, 35,39 and that Cks1 has cell cycle regulatory functions independent of p27 suppression. 19 We also found that under cell culture conditions which stimulate HSC to be recruited into the cell cycle, Cks1 deficiency promotes cell death of MPs upon growth factor withdrawal. One possible explanation could be the accumulation of p27, as p27 Figure 2c).…”
Section: Discussionmentioning
confidence: 61%
“…12 We observed a strong reduction of the total cell numbers in the fetal liver of E14 embryo and the BM of 8-12-week-old Cks1 − / − mice compared with their wt (Cks1 +/+ ) counterparts (Figure 2a). Compared with the 10-20% reduction in body size, 12,19 the distinct reduction in fetal liver (36.0%) and BM (37.7%) cells suggests possible alterations in early hematopoiesis. However, the populations of mature blood cells and the bone structure of Cks1 − / − mice were unchanged, indicating unaltered differentiation of Cks1-deficient HSCs ( Supplementary Figures S2b and c).…”
Section: Ig Controlmentioning
confidence: 90%
See 3 more Smart Citations